Estimativas de parâmetros genéticos para características de crescimento em ovinos da raça somalis brasileira - Magalhães, Ana Fabricia Braga [UNESP]; Lobo, Raimundo Nonato Braga; Facó, Olivardo (FapUNIFESP (SciELO), 2013)
The aim of this study was to estimate genetic parameters for growth traits in Somalis Brasileira hair sheep breed. The data used in this study were from the flock of Embrapa Caprinos and Ovinos, located in the city of Sobral - CE, Brazil. Data contained records of 1,120 animals in the pedigree file. The analyzed traits were birth weight (PN), weaning weight (PD), weight gain from birth to weaning (GND) and adult weight (PA). Estimates of (co)variances and genetic parameters were obtained by Derivative Free Restricted Maximum Likelihood Method (DFREML) using the MTDFREML software. The heritabilities were low to moderate in univariate analysis. The maternal heritabilities were higher than direct heritabilities. The heritabilities in multivariate analysis exceeded those in univariate analysis. The values of genetic correlations varied widely.
Genetic parameters estimates for growth traits in somalis brasileira hair sheep breed
Keywords: Body weight; Genetic correlation; Heritability; Multivariate analysis